PEMANFAATAN DANA ZAKAT PRODUKTIF DALAM TINJAUAN MAQASHID SYARIAH (Studi di Kelurahan Ganting Kecamatan Padang Panjang Timur) - Pegi Elvina Yahya; Nofialdi Nofialdi (Institut Agama Islam Negeri Batusangkar, 2021)
Based on research that there are several mustahiq who divert productive zakat funds for daily food needs, for medical expenses, for education, to repair the kitchen and to pay installments for rented stalls. The reason for mustahiq to transfer productive zakat funds is because there is an urgent need and insufficient income for needs. Based on these reasons, the transfer of productive zakat funds is not contradictory and even in line with the theory of al-maqashid al-syariah. Because for the cost of daily food needs and medical expenses in order to maintain the soul which is classified as an element of daruriyyat (primary needs), the transfer of zakat funds for education costs in order to maintain the mind which is classified as an element of hajiyyat (secondary needs), the transfer of zakat funds to repair the kitchen and pay the daily shop installments which are part of the maintenance of assets belonging to the hajiyyat element (secondary need). While zakat is productive in order to maintain property. Hierarchically, preserving religion takes precedence over preserving the soul, preserving the soul takes precedence over maintaining reason, preserving reason takes precedence over nurturing offspring, preserving offspring takes precedence over preserving property.